CO2-Responsive polymer materials. Issue 1 (22nd August 2016) - Liu, Hanbin; Lin, Shaojian; Feng, Yujun; Theato, Patrick
Abstract : This paper reviews the chemical fundamentals of CO2 -responsive polymers as well as the latest reported "smart" material systems switched by CO2 . Abstract : CO2 -Responsive polymer materials have received enormous attention in recent years, since CO2 as a new trigger has many advantages such as abundant availability, low cost, energy-saving, environment-friendly, non-toxic, good reversibility as well as great biocompatibility. In this review, we first discuss the virtues of CO2 -responsiveness by comparing with traditional stimuli-sensitive materials that respond to pH, light, or redox stimuli. Then, the chemical fundamentals of CO2 -responsive polymer materials are revealed including recently discovered "unexpected" CO2 -sensitive features. Recent progress of CO2 -responsive polymer materials is highlighted followed by various CO2 -responsive "smart" polymer systems. Finally, challenges and outlooks in this area are discussed.